Perancangan Mebel Multifungsi Untuk Villa Grand Trawas Di Mojokerto - Gani Gondo Kusumo (Intra, 2017)
With life that has been getting more modern and advanced lifestyle, people are demanded to be busy with work and often forget the need of resting. When people are resting, they need relaxation. In addition to materials and toys in the shape of furniture, it is also important to consider a detail ergonomic dimension to support comfort in use, so that the purpose of the relaxation can be achieved. This research is supported by data from literature on lounge chairs, and therefor it will obtain a furniture design for villas that are capable of supporting the relaxing function optimally. The lounge chairs have a backrest characteristic with a slope of more than 90 degrees and has a backrest for the feet, so the chairs can sustain the whole body of the user.